Cairo behind the gates: studying the sensory configuration of Al-Rehab City - Noha Gamal Said (Ambiances)
The current research aims to elaborate the sensory configuration of a gated community named Al Rehab City in Cairo. This contemporary urban form, imported from the United States, is part of the last stage of modernizing the city. The methods used are based on analysing the sensory phenomena captured by several techniques in situ, such as participant observation, sound recordings, in addition to citizens’ speech in the form of “commented walks”. In the first phase of analysis, the research identifies the relevant sensory phenomena which are the result of a western urban concept inhabited by oriental society. In the second part we analyse the sensory structure of this urban model by revealing the way in which the body, hearing and sight traverse the various spatial borders which make up this form of habitat.